4.43 Problems 2101 to 2150

   4.43.1 \(y'''(x)-3 y'(x)+2 y(x)=3 e^x\)
   4.43.2 \(y'''(x)-3 y'(x)+2 y(x)=e^x x^2\)
   4.43.3 \(y'''(x)-4 y'(x)=x^2-3 e^{2 x}\)
   4.43.4 \(y'''(x)-7 y'(x)+6 y(x)=0\)
   4.43.5 \(y'''(x)=a^2 y(x)\)
   4.43.6 \(y'''(x)+2 x y'(x)+y(x)=0\)
   4.43.7 \(y'''(x)+2 a x y'(x)+a y(x)=0\)
   4.43.8 \(y'''(x)+y(x) f'(x)+2 f(x) y'(x)=0\)
   4.43.9 \(y'''(x)-y''(x)+y'(x)=0\)
   4.43.10 \(y'''(x)-y''(x)+y'(x)+y(x)=0\)
   4.43.11 \(y'''(x)+y''(x)+y'(x)-3 y(x)=0\)
   4.43.12 \(y'''(x)-y''(x)-2 y'(x)=0\)
   4.43.13 \(y'''(x)-y''(x)-2 y'(x)=e^{-x}\)
   4.43.14 \(y'''(x)+y''(x)+4 y'(x)+4 y(x)=0\)
   4.43.15 \(y'''(x)+y''(x)+2 y'(x)+4 y(x)=\sin (2 x)\)
   4.43.16 \(y'''(x)+y''(x)-7 y'(x)-15 y(x)=0\)
   4.43.17 \(y'''(x)+2 y''(x)+y'(x)=0\)
   4.43.18 \(y'''(x)+2 y''(x)+y'(x)=(x-1) x\)
   4.43.19 \(y'''(x)-2 y''(x)+y'(x)=e^x\)
   4.43.20 \(y'''(x)-2 y''(x)-y'(x)+2 y(x)=\sinh (x)\)
   4.43.21 \(y'''(x)-2 y''(x)-3 y'(x)=0\)
   4.43.22 \(y'''(x)-2 y''(x)-3 y'(x)=3 x^2+\sin (x)\)
   4.43.23 \(y'''(x)-2 y''(x)-3 y'(x)=3 x^2+e^{-x}\)
   4.43.24 \(y'''(x)-2 y''(x)+3 y'(x)+10 y(x)=0\)
   4.43.25 \(y'''(x)-a^2 y'(x)+2 a^2 y(x)-2 y''(x)=0\)
   4.43.26 \(y'''(x)-a^2 y'(x)+2 a^2 y(x)-2 y''(x)=\sinh (x)\)
   4.43.27 \(y'''(x)-3 y''(x)+4 y(x)=0\)
   4.43.28 \(y'''(x)+3 y''(x)-y'(x)-3 y(x)=0\)
   4.43.29 \(y'''(x)-3 y''(x)-y'(x)+3 y(x)=x^2\)
   4.43.30 \(y'''(x)+3 y''(x)-y'(x)-3 y(x)=\cosh (x)\)
   4.43.31 \(y'''(x)+3 y''(x)+3 y'(x)+y(x)=0\)
   4.43.32 \(y'''(x)+3 y''(x)+3 y'(x)+y(x)=e^{-x} x\)
   4.43.33 \(y'''(x)-3 y''(x)+3 y'(x)-y(x)=x \left (1-e^x x^2\right )\)
   4.43.34 \(y'''(x)+3 y''(x)+3 y'(x)+y(x)=e^{-x} \left (2-x^2\right )\)
   4.43.35 \(y'''(x)-3 y''(x)+4 y'(x)-2 y(x)=0\)
   4.43.36 \(y'''(x)-3 y''(x)+4 y'(x)-2 y(x)=e^x+\cos (x)\)
   4.43.37 \(y'''(x)-4 y''(x)+5 y'(x)-2 y(x)=0\)
   4.43.38 \(y'''(x)-4 y''(x)+5 y'(x)-2 y(x)=x\)
   4.43.39 \(y'''(x)-4 y''(x)+6 y'(x)-4 y(x)=0\)
   4.43.40 \(y'''(x)-6 y''(x)+9 y'(x)=0\)
   4.43.41 \(y'''(x)-6 y''(x)+12 y'(x)-8 y(x)=e^{2 x} x^2\)
   4.43.42 \(y'''(x)+a^3 (-y(x))+3 a^2 y'(x)-3 a y''(x)=0\)
   4.43.43 \(y'''(x)+a^3 (-y(x))+3 a^2 y'(x)-3 a y''(x)=e^{a x}\)
   4.43.44 \(y'''(x)=a y''(x)\)
   4.43.45 \(y'''(x)+\text {a1} y''(x)+\text {a2} y'(x)+\text {a3} y(x)=0\)
   4.43.46 \(y'''(x)-2 \left (-2 a-4 x^2+1\right ) y'(x)-8 a x y(x)-6 x y''(x)=0\)
   4.43.47 \(y'''(x)+a^3 x^3 y(x)+3 a^2 x^2 y'(x)+3 a x y''(x)=0\)
   4.43.48 \(y'''(x)+x^2 \left (-y''(x)\right )+2 x y'(x)-2 y(x)=0\)
   4.43.49 \(y'''(x)+y''(x) (2 \cot (x)+\csc (x))-y'(x)=\cot (x)\)
   4.43.50 \(y'''(x)-\sin (x) y''(x)-2 \cos (x) y'(x)+y(x) \sin (x)=\log (x)\)